The Application of Artificial Intelligence in The Field Of Gaming - Fu, Yuhao (Transactions on Computer Science and Intelligent Systems Research, 2024)
In recent years, the landscape of the electronic gaming industry has been profoundly reshaped by advancements in computer hardware and software capabilities. Notably, the proliferation of network and mobile gaming platforms has catalyzed unprecedented growth within the sector. This surge in popularity underscores the increasing demand for immersive and engaging gaming experiences across diverse demographics. This paper endeavors to delve into the intricacies of AI’s role in gaming, providing an in-depth exploration of its core processes and application methodologies. Specifically, it aims to elucidate how AI techniques are leveraged to create intelligent characters and generate dynamic content, thereby enriching the gaming experience. By examining real-world examples of AI integration in gaming and forecasting future trends, this paper seeks to offer valuable insights into the evolving intersection of technology and entertainment.As technologies such as deep learning and neural networks continue to evolve, the application of AI in games will also become more intelligent and adaptive, able to adjust the gaming experience in real time based on player behavior and preferences.